TS2: a realistic IEEE1588 time-synchronization simulator for mobile wireless sensor networks. (February 2015) - Huang, Yiwen; Li, Taihua; Dai, Xuewu; Wang, Haowen; Yang, Yang
This paper presents the development of a simulator, TS2 (time-synchronization simulator), for realistically simulating and studying the performance of the IEEE 1588 precise time protocol (PTP) in IEEE 802.15.4 (TI CC2420 chip)-based mobile wireless sensor networks (WSNs). The PTP has the advantage of achieving high time precision at a low cost. It was designed for a wired Ethernet with requirements of symmetric communication paths and accurate time stamping, which is difficult for the low-cost WSNs to meet, as WSNs suffer more from overwhelming transmission delay jitters. An analytic solution to the performance of the PTP in WSNs is not possible, and it is of importance to evaluate the performance by realistic simulation. Based on the open-source OMNeT++ simulation engine, a realistic simulator was developed to simulate the PTP in IEEE 802.15.4 networks. There are two main contributions and benefits of the developed simulator. (1) Reality and fidelity: the WSN node's various layers (including radio channels and TI CC2420 chip), drifting oscillator clocks and PTPs are simulated realistically. The drifting clock is simulated at an adjustable and higher resolution. (2) Support to both hardware and software time stamping, and the time-stamping uncertainties, by using a separated modular time-stamping module. It also has other features (such as extendibility and code-reusability, mobile WSN nodes, scalability for multi-node, multi-hop simulation). Finally, to demonstrate the simulator's application to evaluating a PTP-based clock correction algorithm, a direct servo clock adjustment algorithm (i.e., a P controller) for a TI CC2420-based WSN was simulated and its performance was analyzed.